Eficacia de alternativas fisionutricionales sobre la capacidad de rebrote y rendimiento del pasto guinea (Megathyrsus maximus (Jacq.) B.K.Simon & S.W.L.Jacobs.) en secano - Vélez Mora, Roberth Armando (2021)
The objective of the research was to evaluate the efficacy of physio-nutritional alternatives on the regrowth capacity and yield of guinea grass in rainfed conditions. The experiment was developed during the dry season of 2020 in the town of Figueroa in Bolívar canton, Manabí. The evaluated treatments were T1 (NPK + K amino acid + Bioregulators + OM + Hydrogel); T2 (K amino acid + Bioregulators + OM + Hydrogel); T3 (Bioregulators + OM + Hydrogel); T4 (OM + Hydrogel); T5 (Hydrogel) and T6 (Control). The main variables recorded were dry matter production (t ha- 1), pasture recovery time (days) and protein content (%). The results obtained highlight that the T1 treatment reached the highest dry matter production with 17.66 t ha-1, which meant an increase of 39% in relation to the control treatment. The T1 treatment also reached the highest protein concentration with 14.68%, which denotes an increase of 51%, in relation to the control treatment that barely achieved 7.13%. Likewise, the T1 treatment showed the shortest recovery time of the grass with 42 days, in contrast to the control treatment whose recovery time lasted up to 68 days. It is concluded that NPK fertilization, plus the application of hydrogel, OM and foliar cocktails based on K amino acids and bioregulators, is efficient for the production of savoy grass under dry conditions.